AMENABLE WEIGHTED HYPERGROUPS (Journal of Sciences, Islamic Republic of Iran)
In this paper among many other things we prove that the topological left amenability and left amenability of a weighted hypergroup (K, ?) are equivalent. For a normal subgroup H of K, we define a weight function ?? on KIH and obtain connection between left amenability of (K, ?) and (K|H, ??). Let H be a compact subhypergroup of K. We define the weight function on K||H and obtain connection between left amenability of (K, ?) and (KIIH,??).